Pengaruh Brand Image dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Kosmetik Wardah (Studi pada Perempuan Muslim di Kota Bogor) - Habibah Habibah; Ikhwan Hamdani; Santi Lisnawati (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
The more advanced development of science and technology makes every cosmetic company to create a good brand image so it can provide the attraction of purchasing decision through the use of celebrity endorsers. This article aims to determine the effect of brand image and celebrity endorser on the purchasing decision of wardah cosmetic (based on the study of Muslimah in Bogor). The population in this article is muslimah in Bogor who have bought and used wardah cosmetic, and 100 muslimah as the sample. The sampling technique used is non-probability sampling. The data used in this article are primary and secondary data. The data analysis technique used is descriptive analysis and multiple linear regression analysis using the SPSS 16 program.